Economic valuation of effects on health within Health Impact Assessments (Italian Journal of Public Health, 2007)
Public health experts widely agree that policies, programs and projects from numerous sectors have a decided influence on health determinants, hence the surge of interest in prospective “Health Impact Assessments” (HIA). Likewise, economic considerations currently pose a major challenge throughout the field; health economists developed a range of approaches to calculate (in)direct costs of diseases, treatments etc. The question arises then, if and how can economic valuation of health effects within HIAs take place now or in the future. To investigate this issue, the Department of Public Health, University Bielefeld, along with the Institute of Public Health North-Rhine Westphalia (loegd), Germany, conducted an email-survey. The answers of 68 participating experts and practitioners from 16 countries and from international organizations showed that so far, only a small fraction of them (7%) have conducted economic valuations; more than one third (37%), however, at least sometimes discusses this option. The main obstacles seem to be: lack of knowledge about methodological details, existing uncertainties, and various problems in defining economic value for effects on health. Cost-benefit, cost-effectiveness, and cost-utility analysis were nominated most frequently as candidate methods. Participants also provided nearly 300 commentaries concerning potentials and/or risks that these economic valuations might have. This paper is mostly about the basic and quantitative results from the survey; it is planned to publish the qualitative results (with detailed discussion of the range of arguments “pro” and “con”) in a separate paper.
Keywords: Health Impact Assessment; economic valuation; Cost-benefit analysis; E-mail survey